A THREE YEAR EXPERIENCE WITH CONVENTIONAL THYROIDECTOMY (SUBTOTAL THYROIDECTOMY) IN THE MANAGEMENT OF SIMPLE GOITRES IN BINGHAM UNIVERSITY TEACHING HOSPITAL JOS. - Nimkur, Tonga; Chukuma , Okoye; Modu , Audu; Nyam, Zang Chuwang (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
Introduction:-Thyroidectomy is the surgical procedure for the reduction or total removal of the thyroid gland – to achieve aesthesis or functional changes resulting from enlargement and pressure on the trachea or hyper function of the gland. Thyroidectomy as a procedure has developed significantly due to more understanding of the anatomy of the neck and the surgical technique.Thyroidectomy has common complications related to the procedure which include – haematoma formation, laryngeal nerve palsy and hypocalcaemia, depending on the nature of the procedure, the expertise of the surgeon involved and the technique. Method:-A retrospective study over a three year period (Jan 2018-Dec 2020). Case notes were retrieved and the gender, age, indications, outcome of surgeries noted and analysed with the aim of highlighting the complications observed with conventional thyroidectomy in line with the expertise of the surgeon, the use of nerve monitor, pre/post operative vocal cord assessment and the use of suction drain to eliminate or reduce the complications. Results: - 48cases were included in the study, 42 females(87.5%) and 6 males (12.5%);male: female=1:7. Age range is 17to 60 years (mean age-39.48). Patients were all euthyroid before surgery, all were FNAC negative for malignant features, subtotal thyroidectomy was performed for all patients, no permanent laryngeal nerve palsy or permanent hypocalcaemia and no haematoma formation in this study. Conclusion:- Conventional thyroidectomy in a less technologically advanced environment with less prospects of replacement therapy can be practiced safely with minimal complications.